2012
DOI: 10.1007/s11368-012-0579-9
|View full text |Cite
|
Sign up to set email alerts
|

Humus accumulation, humification, and humic acid composition in soils of two post-mining chronosequences after coal mining

Abstract: Purpose To assess how the rates of humus formation and humification are affected by land use and age of ecosystems, this study investigated soil development in two post-mining chronosequences (spoil heaps formed from open-cast coal mining near Sokolov, Czech Republic). The following characteristics were measured: content, composition, and properties of humic acids; organic carbon (C) and total nitrogen (N) contents; pH; and amorphous iron content. Materials and methods Two chronosequences were studied. One con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 23 publications
1
44
0
1
Order By: Relevance
“…There is a high probability that the Cd accumulated in roots (in the hydroponic cultivation stage) could have accelerated the aging and dying of the root material. Root exudates and dead roots are known to be good sources of carbon and energy for soil microorganisms, and, together with microbial metabolites, are substrates for humification, raising the amounts of soil organic carbon (Abakumov et al 2013). In such cases, during humus accumulation, metal-organic complexes can also be incorporated into soil organic matter (Renella et al 2004, Semenov et al 2013.…”
Section: Organic Carbon Concentration In Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a high probability that the Cd accumulated in roots (in the hydroponic cultivation stage) could have accelerated the aging and dying of the root material. Root exudates and dead roots are known to be good sources of carbon and energy for soil microorganisms, and, together with microbial metabolites, are substrates for humification, raising the amounts of soil organic carbon (Abakumov et al 2013). In such cases, during humus accumulation, metal-organic complexes can also be incorporated into soil organic matter (Renella et al 2004, Semenov et al 2013.…”
Section: Organic Carbon Concentration In Soilmentioning
confidence: 99%
“…They increase the resistance of the upper soil layer to water and wind erosions (Ernst 2005, Beats et al 2006, and together with rhizospheric microorganisms, act as factors in accelerating the rates of plant residue degradation and in encouraging humus accumulation (Abakumov et al 2013). The water-soluble root exudates and mucilage of fully functional roots, the sloughing of root cells, as well as the accumulation of dead roots are sources of organic carbon and energy for rhizospheric microorganisms (Hütsch et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing studies have demonstrated that the humus content and componential properties exhibited considerable specificity in different forests (Dong et al, 2015;Li et al, 1992). In addition, the humus properties were also significantly changed during the process of forest development and aging or when the dominant species in forests were changed (Abakumov et al, 2013;Cerli et al, 2008;Descheemaeker et al, 2009;Labaz et al, 2014;Trap et al, 2013). Noticeably, the longterm growth of pure forests sometimes will cause the losses of humus components and alterations of humus structure properties in soil (Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Eleven peer-reviewed papers are being published in this special issue of the Journal of Soils and Sediments, which focus on the properties, processes, evolution, and management of soils in urban and human-altered environments. Targets of study include soils with technic materials (Abakumov et al 2013;El Khalil et al 2013;Houben et al 2013;Huot et al 2013;Nehls et al 2013;Schonsky et al 2013), those with elevated metal contents (Aboudrar et al 2013;Jean-Soro et al 2013), soils in storm water infiltration basins (Coulon et al 2013;El-Mufleh et al 2013), and soils with landmines (Preetz et al 2013).…”
mentioning
confidence: 99%